1995
DOI: 10.1149/1.2049976
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Titanium in Molten 2AlCl3 ‐ NaCl

Abstract: The electrochemistry of titanium has been examined in 2A1C13-NaC1 electrolyte. Titanium may be oxidized to yield Ti(II), Ti(III), and Ti(IV) complexes. The divalent species may be used to eleetrodeposit A1-Ti alloys, while the trivalent species is sparingly soluble. Cyclic voltammetry on a tungsten electrode in solutions with varying Ti(II) concentration has been used to examine the kinetics of the precipitation reaction associated with Ti(III). The induction time required for precipitation is dependent upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 10 publications
6
39
0
Order By: Relevance
“…This behavior is a common feature of overpotential alloy deposition in chloroaluminate melts and was observed during the electrodeposition of Al-Cr 20,21 Al-Mn, 23,44 Al-Mo, 45 and Al-Ti. 24,25,39,46 The finding that plating solutions containing Zr͑IV͒ lead to alloys with higher Zr content than plating solutions containing equal concentrations of Zr͑II͒ may be reconciled by considering the diffusion coefficient data in Table I. Because the concentration-dependent diffusion coefficient for Zr͑II͒ is only a small fraction of that for Zr͑IV͒, the observed inefficiency of Zr͑II͒ for plating Al-Zr alloys must be directly related to the mass-transport limitations imposed by the diminutive diffusion coefficient of the latter species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is a common feature of overpotential alloy deposition in chloroaluminate melts and was observed during the electrodeposition of Al-Cr 20,21 Al-Mn, 23,44 Al-Mo, 45 and Al-Ti. 24,25,39,46 The finding that plating solutions containing Zr͑IV͒ lead to alloys with higher Zr content than plating solutions containing equal concentrations of Zr͑II͒ may be reconciled by considering the diffusion coefficient data in Table I. Because the concentration-dependent diffusion coefficient for Zr͑II͒ is only a small fraction of that for Zr͑IV͒, the observed inefficiency of Zr͑II͒ for plating Al-Zr alloys must be directly related to the mass-transport limitations imposed by the diminutive diffusion coefficient of the latter species.…”
Section: Resultsmentioning
confidence: 99%
“…For Ti͑II͒, this phenomenon is attributed to polymerization of the Ti͑II͒ species as ͓Ti͑AlCl 4 ) 2 ] m , with m increasing as the Ti͑II͒ concentration is increased. 25,39,42,43 Given the overall similarity of the chemistry of Ti͑II͒ and Zr͑II͒, polymerization of Zr͑II͒ is also expected. The observed concentration dependence of E 1/2 for the first Zr͑II͒ oxidation waves, but not the second waves, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ti (IV) first reduced to Ti (III) and then subsequently reduced to Ti (II). However, other studies [9,10,12] showed that, when the concentration of Ti (III), i.e., b-TiCl 3 , exceeded the solubility limit, then Ti (III) was passivated on the electrode surface and was also precipitated. This passive film blocks the electrodes and prevents oxidation and reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical behavior of titanium in Lewis acidic chloroaluminate melt was investigated. [10][11][12][13][14][15] The electrochemistry of TiCl 4 in strongly Lewis acid molten salt (AlCl 3 -EtMelmCl) at room temperature was reported by Carlin et al [13] It was found that the reduction of tetravalent titanium Ti (IV) occurs in two one-electron steps. Ti (IV) first reduced to Ti (III) and then subsequently reduced to Ti (II).…”
Section: Introductionmentioning
confidence: 99%
“…A three-step reduction of Ti 4+ to metal, Ti 4+ → Ti 3+ → Ti 2+ → Ti, is well known as the reduction mechanism [2][3][4][5][6][7][8][9]. The current efficiency was low, while sludge formation occurred.…”
Section: Introductionmentioning
confidence: 99%